How are companies addressing supply chain transparency?: pedagogical case study of Rügenwalder Mühle - Theiner, Julia (2021)
In the wake of further development of appropriate technologies and reports about food contamination incidents, human rights abuses, and environmental impacts, supply chain transparency in the food industry is gaining more attention. Customers demand more information and new governmental regulations were prescribed. Furthermore, companies can benefit from transparent supply chains as opportunities to increase efficiency can be revealed and risks can be managed more easily. However, many companies struggle to build transparent supply chains as it comes with several requirements and challenges. This pedagogical case study is about a German traditional meat company that successfully launched vegetarian and vegan substitutes in 2014 and is today the market leader in the sector in Germany. The case study applies frameworks from strategic management theory on the company’s endeavor to establish a new transparent supply chain structure for its meat substitutes. External factors supporting or impeding the undertaking will be explored and relevant internal factors will be identified and reviewed on their ability to ensure sustained competitive advantage. A detailed case description of the company establishing the context of the topic and a comprehensive literature review on supply chain transparency are provided. The study is a problem-based instructional approach situating learning in a practical task. The implementation in education imparts students with several diverse skills like critical and analytical thinking, information evaluation, and in case of group work, what is recommended to maximize learning effects, numerous interpersonal skills. It was designed for students but can be integrated into courses in different ways.